The DNA Binding-Independent Function of the Glucocorticoid Receptor Mediates Repression of Ap-1–Dependent Genes in Skin - Tuckermann, Jan; Reichardt, Holger Michael; Schütz, Günther; Angel, Peter (The journal of cell biology, 1999)
The glucocorticoid receptor (GR) mediates the biological effects of glucocorticoids (GCs) through activation or repression of gene expression, either by DNA binding or via interaction with other transcription factors, such as AP-1. Work in tissue culture cells on the regulation of AP-1–dependent genes, such as collagenase (MMP-13) and stromelysin (MMP-3) has suggested that the antitumor and antiinflammatory activity of GCs is mediated, at least in part, by GR-mediated downmodulation of AP-1. Here, we have identified phorbol ester-induced expression of MMP-3 and MMP-13 in mouse skin as the first example of an in vivo system to measure negative interference between AP-1 and GR in the animal. Cell type-specific induction of these genes by tumor promoters is abolished by GCs. Importantly, this is also the case in GRdim mice expressing a DNA binding-defective mutant version of GR. In contrast, the newly identified target genes in skin, plasma glutathione peroxidase and HSP-27, were induced by GC in wild-type, but not in GRdim mice. Thus, these data suggest that the DNA binding-independent function of the GR is dispensable for repression of AP-1 activity in vivo and responsible for the antitumor promoting activity of GCs.